Effectiveness of B-actin promoter on driving target gene expression in common carp transgenesis - Hidayani, Andi Aliah; Carman, Odang; Alimuddin, . (Indonesian Society of Scientific Aquaculture (ISSA), 2011)
Promoter in transgene construct plays an important role on regulating of transgene expression level in transgenic fish. In fish transgenesis, researcher convinced that use all-fish gene construct is safety and prospective. This study was performed to compare effectiveness b-actin promoter, - the promoter which has ubiquitous, constitutive, housekeeping characteristics, from common carp (homologous) and from tilapia and medaka b-actin promoters (heterologous) in driving of green fluorescent protein (GFP) expression as a model of target gene on common carp transgenesis. These gene constructs were separately microinjected into cytoplasm of 60 one-cell-stage common carp embryos. The results suggested that 70% survival rate at embryo stage and 45% hatching rate values showed that the microinjection was performed successfully. Percentage of embryos expressing GFP gene were slightly higher when injected using common carp and medaka promoters than those of using tilapia promoter. Percentage of larvae expressing GFP using common carp promoter was similar with medaka promoter. Furthermore, GFP expression using common carp b-actin promoter could be detected at one-week-old larvae, while GFP expressing using medaka b-actin promoter was lasted at 2-day-old larvae. The results demonstrated that homologous promoter more effective in driving of a target gene expression than that of heterologous promoter. Key words: homologous promoter, GFP, transgenesis, common carp ABSTRAK Promoter dalam konstruksi transgen berperan penting dalam pengaturan tingkat ekspresi transgen pada ikan transgenik. Dalam transgenesis ikan, peneliti meyakini bahwa penggunaan konstruksi gen